El Principio de Consentimiento en la Actualidad: Cómo el Principado de Liechtenstein Reivindica las Tesis de Juan de Mariana sobre el Gobierno - Gonzalo, Marcos Benjamín (Journal of the sociology and theory of religion, 2022)
Well-known are the contributions to social and legal sciences made by the Spanish scholastics. Specifically, in regard to political science, their ideas against the rampant absolutism of the time stand out, for they vehemently defended that society and its institutions -specially the institution of private property-existed previously to the State. Noteworthy are the ideas of Jesuit Juan de Mariana about the adequate functions of Government as well as their wide limitations, always contingent in their mandates to their subjects’ consent (the "principle of consent"). Not only was Father Juan de Mariana ahead of the principles of American constitutionalism, he gave one step further, defending that the overthrow of the governor had he exceeded his functions. The following paper defends that, far from being an anachronistic theory of Government, the ideas defended by the Jesuit are currently claimed by the Principality of Liechtenstein and the political philosophy of the Reigning Prince, Hans-Adam II.